HOW DOES SMALL MEDIUM ENTERPRISE IN DEVELOPING COUNTRIES OVERCOME INFORMATION AND COMMUNICATION TECHNOLOGY ADOPTION PROBLEMS? - Ambar Sari Dewi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
The role of Small Medium Enterprise (SME) has been proven to be important in economic development. Many research also believed that the rapid rise of SME’s development caused by Information and Communication Technology (ICT) adaption in their business. However, its adoption in developing countries faces several problems. Using Rogers’ (1995) diffusion of innovation theory and Manueli’s et.al (2007) recommendations, this essay will argue that to overcome the problem, a strong cooperation should be taken, interpersonal communication should be use as well as type of ICTs should be chosen wisely, based on specifi needs.